A Critical Role of the mTOR/eIF2α Pathway in Hypoxia-Induced Pulmonary Hypertension - Wang, Ai-ping; Li, Xiao-hui; Yang, Yong-mei; Li, Wen-qun; Zhang, Wang; Hu, Chang-ping; Zhang, Zheng; Li, Yuan-jian (PloS one, 2015)
Enhanced proliferation of pulmonary arterial vascular smooth muscle cells (PASMCs) is a key pathological component of vascular remodeling in hypoxia-induced pulmonary hypertension (HPH). Mammalian targeting of rapamycin (mTOR) signaling has been shown to play a role in protein translation and participate in the progression of pulmonary hypertension. Eukaryotic translation initiation factor-2α (eIF2α) is a key factor in regulation of cell growth and cell cycle, but its role in mTOR signaling and PASMCs proliferation remains unknown. Pulmonary hypertension (PH) rat model was established by hypoxia. Rapamycin was used to treat rats as an mTOR inhibitor. Proliferation of primarily cultured rat PASMCs was induced by hypoxia, rapamycin and siRNA of mTOR and eIF2α were used in loss-of-function studies. The expression and activation of eIF2α, mTOR and c-myc were analyzed. Results showed that mTOR/eIF2α signaling was significantly activated in pulmonary arteries from hypoxia exposed rats and PASMCs cultured under hypoxia condition. Treatment with mTOR inhibitor for 21 days attenuated vascular remodeling, suppressed mTOR and eIF2α activation, inhibited c-myc expression in HPH rats. In hypoxia-induced PASMCs, rapamycin and knockdown of mTOR and eIF2α by siRNA significantly abolished proliferation and increased c-myc expression. These results suggest a critical role of the mTOR/eIF2αpathway in hypoxic vascular remodeling and PASMCs proliferation of HPH.